MEMBERDAYAKAN MASYARAKAT UNTUK MENGELOLA SAMPAH ORGANIK DENGAN LUBANG RESAPAN BIOPORI (LRB) - Neneng Mardiah Bukit, Ipak; Nadya, Yusri; Mastura, Lely; Fahriana, Nina (Fakultas Teknik, Universitas Samudra, 2024)
Organic waste become problem in the communities. Ignorance and neglected of this problem leads to public inconvenience due to decay of organic waste. The purpose of this community service is to provide understanding to the community about the importance of managing their household waste independently. Organic waste can be transform to fertilizer by making biopore infiltration holes. In order to do so, our team socializes how to make those holes to the residents of a village in Kota Langsa, thus the community can manage their own domestic waste, eventually the city can reduce waste thrown into landfills. Moreover, biopores infiltration holes can help in conserving groundwater in residential areas, because rainwater is more easily absorbed by the soil